Healthy Gut Microbiome Composition Enhances Disease Resistance and Fat Deposition in Tibetan Pigs - Shang, Peng; Wei, Mingbang; Duan, Mengqi; Yan, Feifei; Chamba, Yangzom (Frontiers in Microbiology, 2022)
The gut microbiota is involved in a range of physiological processes in animals, and modulating the microbiome composition is considered a novel target for identifying animal traits. Tibetan pigs show better fat deposition and disease resistance compared to Yorkshire pigs. However, studies investigating the correlation between favorable characteristics in Tibetan pigs and the gut microbial community remains scarce. In the current study, 1,249,822 high-quality sequences were obtained by amplicon sequencing of the colon contents of Tibetan and Yorkshire pigs. We found that the abundance and relative abundance of colonic microbiota in Tibetan pigs were higher than in Yorkshire pigs. At the phylum level, Firmicutes were the dominant colonic microflora of Tibetan and Yorkshire pigs, and the ratio of Firmicutes to Bacteroides in Tibetan pigs was slightly higher than in Yorkshire pigs. Actinobacteria and Spirobacteria were significantly higher in Tibetan pigs than in Yorkshire pigs. At the genus level, the relative abundance of Bifidobacterium, Lactobacillus, and Bacteriologist, which are related to disease resistance, was significantly higher than in Yorkshire pigs. In conclusion, the composition and abundance of colonic intestinal microflora in Tibetan pigs were closely related to their superior traits. Bifidobacteria, Ruminococcaceae, and Family-XIII-AD3011-Group are conducive to improving disease resistance in Tibetan pigs. Lactobacillus and Solobacterium were observed to be the main bacterial communities involved in fat deposition in Tibetan pigs. This study will provide a new reference for the development and utilization of Tibetan pigs in future.